Galectin-3 Involvement in Cognitive Processes for New Therapeutic Considerations - Mijailović, Nataša R.; Vesic, Katarina; Arsenijevic, Dragana; Milojević-Rakić, Maja; Borovcanin, Milica M. (Frontiers in Cellular Neuroscience, 2022)
Abstract: Cognitive impairment may be a consequence of the normal aging process, but it may also be the hallmark of various neurodegenerative and psychiatric diseases. Early identification of individuals at particular risk for cognitive decline is critical, as it is imperative to maintain a cognitive reserve in these neuropsychiatric entities. In recent years, galectin-3 (Gal-3), a member of the galectin family, has received considerable attention with respect to aspects of neuroinflammation and neurodegeneration. The mechanisms behind the putative relationship between Gal-3 and cognitive impairment are not yet clear. Intrigued by this versatile molecule and its unique modular architecture, the latest data on this relationship are presented here. This mini-review summarizes recent findings on the mechanisms by which Gal-3 affects cognitive functioning in both animal and human models. Particular emphasis is placed on the role of Gal-3 in modulating the inflammatory response as a fine-tuner of microglia morphology and phenotype. A review of recent literature on the utility of Gal-3 as a biomarker is provided, and approaches to strategically exploit Gal-3 activities with therapeutic intentions in neuropsychiatric diseases are outlined.